Eletromigração controlada em dispositivos de micropontes de alumínio e bismuto - Mistura, Marcos Vasconcellos (Universidade Federal de São Carlos, 2025)
Electromigration is a phenomenon where atoms move within a material due to the application of high electric current densities. This effect can lead to the formation of voids and atomic accumulations, resulting in failures in electronic devices. However, when controlled, electromigration can be used to modify materials at the atomic scale. In this work, we investigated the effects of electromigration on bismuth microbridges, a material of technological interest due to its properties as a topological insulator. As a first step, we performed electromigration on aluminum metal devices, demonstrating the feasibility of precisely controlling this process. The results obtained were consistent with the literature, reinforcing the reliability of the methodology we adopted. Next, we applied the protocol to bismuth, whose semiconductor characteristics imposed additional challenges in controlling electromigration. To overcome these difficulties, we tested various experimental conditions, varying electropulsing parameters, temperature, and atmosphere. Initially, we conducted electromigration at ambient conditions, adjusting the protocol to reach higher temperatures due to the influence of the Joule effect in the experiment. Subsequently, we carried out tests under low pressure and at 350 K, seeking greater control of the process. The results indicated a promising pathway to modify bismuth properties in a controlled manner, although precise control of electromigration is not yet fully established. These advances outline perspectives for future experiments, allowing for parameter optimization and a deeper understanding of the mechanisms governing electromigration in bismuth, aiming for applications in devices based on this material.
Controlled electromigration in aluminum and bismuth microbridge devices
Keywords: Eletromigração; Electromigration; Microbridge devices; Bismuth devices; Dispositivos de bismuto; CIENCIAS EXATAS E DA TERRA::FISICA::FISICA DA MATERIA CONDENSADA::TRANSP.ELETRONICOS E PROP. ELETRICAS DE SUPERFICIES;INTERFACES E PELICULAS